Pengukuran Tinggi Badan (TB), Berat Badan (BB) & Lingkar Lengan Atas (LILA) di Masa Pandemi: Measurement of Height, Weight & Upper Arm Circumference During a Pandemic - Yane Tambing; Mona Safitri Fatiah; Lisda Oktavia Madu Pamangin (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
The problem of children's nutritional status in Indonesia is still fairly high, especially in the eastern region. One of the contributors to the high case is Sarmi Regency, Papua Province. The purpose of this activity was to look at the nutritional status of under-five children in Sarmi Regency through height, weight, and upper-arm circumference. This activity was carried out for 2 weeks, from July 5 - 21, 2021, in Siaratesa Village, Tafarewar, Nengke, and Bebon Jaya, Sarmi Regency with the target of this activity was mothers who have under-five children. This activity was carried out by community education methods, data collection, and measurement practices in the form of height, weight, and upper-arm circumference. The results of this activity obtained wasting cases of 54.1% stunting & underweight 24.1%, and the average upper-arm circumference was about 14.40 cm. Thus, it is expected that there are continuous activities carried out by the local health center to complement the activities as an effort to increase maternal knowledge to guide the occurrence of nutrition in under-five children.   ABSTRAK Masalah gizi pada balita di Indonesia masih menjadi topik yang masih hangat yang masih diperbincangkan, dimana kasus tersebut masih terbilang masih sangat tinggi, terutama di wilayah timur Indonesia, salah satu penyumbang kasus tersebut adalah Kabupaten Sarmi, Provinsi Papua. Tujuan dari kegiatan ini adalah untuk melihat status gizi balita di Kab. Sarmi melalui pengukuran Tinggi Badan (TB), Berat Badan (BB) dan Lingkar Lengan Atas (LILA) balita. Kegiatan ini dilakukan selama ± 2 minggu, pada tanggal 5 – 21 Juli 2021, di Kampung Siaratesa, Tafarewar, Nengke dan Bebon Jaya, Kabupaten Sarmi dengan sasaran kegiatan ini adalah ibu yang memiliki balita yang berusia 0 – 59 bulan. Kegiatan ini dilakukan dengan metode pendidikan masyarakat, pengumpulan data dan praktik pengukuran berupa TB, BB dan LILA. Hasil dari kegiatan ini diperoleh kasus wasting sebesar 54,1 persen, stunting & underweight sebesar 24,1 persen serta rata-rata LILA balita sekitar 14,40 cm. Dengan demikian, diharapkan adanya kegiatan yang berkesinambungan yang dilakukan oleh pihak puskesmas setempat untuk melengkapi kegiatan sebagai upaya meningkatkan pengetahuan ibu dalam upaya menurunkan kejadian masalah gizi pada balita.